Real-Time Image Mosaicing Using Non-rigid Registration - Castanheira de Souza, Rafael Henrique; Okutomi, Masatoshi; Torii, Akihiko (Advances in Image and Video Technology, 2011)
Mosaicing is a classical application of image registration where images from the same scene are stitched together to generate a larger seamless image. This paper presents a real-time incremental mosaicing method that generates 2D mosaics by stitching video key-frames as soon as they are detected. The contributions are three-fold: (1) we propose a “fast” key-frame selection procedure based solely on the distribution of the distance of matched feature descriptors. This procedure automatically selects key-frames that are used to expand the mosaics while achieving real-time performance; (2) we register key-frame images by using a non-rigid deformation model in order to “smoothly” stitch images when scene transformations can not be expressed by homography: (3) we add a new constraint on the non-rigid deformation model that penalizes over-deformation in order to create “visually natural” mosaics. The performance of the proposed method was validated by experiments in non-controlled conditions and by comparison with the state-of-the-art method.